The Effect of Apex Pruning on Vegetative and Generative Growth of Roselle (Hibiscus sabdariffa L.) - Slamet Susanto; Titistyas Gusti Aji; Arifah Rahayu (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTThe experiment was aimed at studying the effect of number of branch on vegetative and generative growth of roselle. The experiment was conducted at Cikabayan Experimental Farm from February to June 2009. The experiment was arranged in randomized complete block design with single factor and consisted of four levels of pruning: control (without pruning), apex pruning with 5 branches, apex pruning with 10 branches, and apex pruning with 15 branches, each with three replications. The result indicated that pruning with different number of branch gave effect on decreasing on some variables of vegetative and generative growth of roselle. Plants experienced apex pruning with 15 branches did not show any differences on number of primary stems, number of secondary stems, number of leaves, number of flowers, fresh and dry weight of calyxes, and anthocyanin content in calyxes. Plants experienced pruning with different number of branches tended to have higher anthocyanin content than those on control. Generally, plants with 15 primary branches gave the best effect on both vegetative and generative growth of roselle.Keywords: Hibiscus sabdariffa L., pruning, branch, growth ABSTRAKPenelitian ini bertujuan untuk mempelajari pengaruh jumlah cabang pada pertumbuhan vegetatif dan generatif rosela. Penelitian dilaksanakan di Kebun Percobaan Cikabayan pada bulan Februari sampai Juni 2009. Percobaan disusun dalam rancangan acak lengkap dengan faktor tunggal dan terdiri dari empat tingkat pemangkasan: kontrol (tanpa pemangkasan), pemangkasan pucuk dengan 5 cabang, pemangkasan pucuk dengan 10 cabang, dan pemangkasan pucuk dengan 15 cabang, masing-masing dengan tiga ulangan. Hasil penelitian menunjukkan bahwa pemangkasan dengan nomor yang berbeda dari cabang memberi efek pada penurunan pada beberapa variabel pertumbuhan vegetatif dan generatif rosela. Tanaman dengan pemangkasan pucuk pada 15 cabang tidak menunjukkan perbedaan pada jumlah batang utama, jumlah sekunder batang, jumlah daun, jumlah bunga, berat segar dan kering calyxes, dan konten antosianin di calyxes. Tanaman mengalami pemangkasan dengan nomor yang berbeda dari cabang cenderung memiliki konten antosianin lebih tinggi dibandingkan pada kontrol. Umumnya, tanaman dengan 15 cabang utama memberikan efek terbaik pada kedua pertumbuhan vegetatif dan generatif rosela.Kata kunci: Hibiscus sabdariffa L., pemangkasan, cabang, pertumbuhan